Fat-soluble vitamin deficiency in children and adolescents with cystic fibrosis. Issue 7 (7th April 2014) - Rana, Malay; Wong-See, Denise; Katz, Tamarah; Gaskin, Kevin; Whitehead, Bruce; Jaffe, Adam; Coakley, John; Lochhead, Alistair
Abstract : Aims: Determine the prevalence of fat-soluble vitamin deficiency in children with cystic fibrosis (CF) aged ≤18 years in New South Wales (NSW), Australia, from 2007 to 2010. Methods: A retrospective analysis of fat-soluble vitamin levels in children aged ≤18 years who lived in NSW and attended any of the three paediatric CF centres from 2007 to 2010. An audit of demographic and clinical data during the first vitamin level measurement of the study period was performed. Results: Deficiency of one or more fat-soluble vitamins was present in 240/530 children (45%) on their first vitamin level test in the study period. The prevalence of vitamins D and E deficiency fell from 22.11% in 2007 to 15.54% in 2010, and 20.22% to 13.89%, respectively. The prevalence of vitamin A deficiency increased from 11.17% to 13.13%. Low vitamin K was present in 29% in 2007, and prevalence of prolonged prothrombin time increased from 19.21% to 22.62%. Fat-soluble vitamin deficiency is present in 10%–35% of children with pancreatic insufficiency, but only a very small proportion of children who are pancreatic-sufficient. Conclusions: This is one of few studies of fat-soluble vitamin deficiency in children with CF in Australia. Fat-soluble vitamin testing is essential to identify deficiency in pancreatic-insufficient children who may be non-compliant to supplementation or require a higher supplement dose, and pancreatic-sufficient children who may be progressing to insufficiency. Testing of vitamin K-dependent factors needs consideration. Further studies are needed to monitor rates of vitamin deficiency in the CF community.